Effect of sky fruit’s seed powder on stability of muffin / Amir Mohd Aisha Nuddin - Mohd Aisha Nuddin, Amir (Faculty of Applied Sciences, 2012)
The aim of this study is to determine the effect of sky fruit’s seed on stability of muffin. In this study the seeds of sky fruit or Swietenia macrophylla were used to analysed its effect on the quality of muffin. The sky fruit’s seed were dried slightly and ground into a fine powder form. The powder was analysed for its total phenolic and saponin content. Analysis of oxidative stability was done on muffins added with the sky fruit’s seed powder and acceptance test was also been done on the muffins. For the total phenolic content of the seed’s powder analysed by using spectrophotometer and gallic acid standard curve. The result shows that the total phenolic compound in the powder was 482.47 + 47.12 mgGAE/100 g. Saponin content was analysed using gravimetric method and the result obtained was 418.62 + 68.71 mg/100 g saponin. Four formulation of muffin with no powder added as control, 50 ppm, 100 ppm and 500 ppm seed’s powder was prepared. Acid value and peroxide value test been done for 12 days and rancimat test also been done on extracted muffin’s oil. For all the analysis, the highest oxidative stability in the 500 ppm muffin. Acceptance test on the taste of muffin was conducted on 25 panellist shows that controlled formulation with no seed’s powder added receive the highest acceptance test. For 50 ppm muffin, 20% of the panellists was able to detect the bitterness of the sky fruit powder in the muffin. Studies show that sky fruit’s seed powder have positive effect on oxidative stability but its bitterness affects the muffin taste hence reduce the suitability of the powder to be used in food product.